Differentiation of Nigella sativa seeds from four different origins and their bioactivity correlations based on NMR-metabolomics approach - Maulidiani, M.; Sheikh, Bassem Y.; Mediani, Ahmed; Leong, Sze Wei; Ismail, Intan Safinar; Abas, Faridah; Lajis, Nordin (Elsevier, 2015)
Authenticity and quality coherence are the major elements in ensuring the consistency of the expected beneficial outcomes from the use of traditional or herbal remedies. Metabolomics offers the possibility of addressing these issues. Principal Component Analysis (PCA) was applied to select the best solvent system for sample extraction. Partial Least Square (PLS) regression analysis was found useful in evaluating the relationship between Nigella sativa seeds from four different origins on the basis of their metabolite profiles. In this study, different bioactivities were displayed by different samples with the Qasemi and Syrian samples exhibited high α-glucosidase inhibitory activity, which was correlated to the high fatty acid contents based on the PLS model. The Ethiopian sample exhibited high DPPH radical scavenging and nitric oxide (NO) inhibition activities, which may be related to the presence of high levels of thymoquinone and thymol. The method was also successfully used to classify “new test” samples into their proper groups.